Synthesis and absolute configuration of cyclic synthetic cathinones derived from α-tetralone - Paškan, Martin; Dobšíková, Kristýna; Kuchař, Martin; Setnička, Vladimír; Kohout, Michal (Chirality, 2024)
The emergence of new synthetic cathinones continues to be a matter of public health concern. In fact, already known products (drugs) are being rapidly replaced by new structurally related alternatives, whereby modifications in the basic cathinone structure are used by manufacturers to circumvent the legislation. On the other hand, some derivatives of synthetic cathinones represent important pharmaceuticals with antidepressant properties. In the search for pharmaceutically relevant analogs, the main goal of the present study was to design and characterize novel cyclic α-tetralone-based derivatives of synthetic cathinones. We synthesized a series of derivatives and verified their chemical structure. Subsequently, chiral separation has been accomplished by high-performance liquid chromatography (HPLC) equipped with a circular dichroism (CD) detector, which directly provided CD spectra of the enantiomers of the analyzed substances at 252 nm. Using density functional theory calculations, we have obtained stable conformers of selected enantiomers in solution and their relative abundances, which we used to simulate their spectra. The experimental and calculated data have been used to assign the absolute configuration of six as-yet unknown synthetic cathinones.
Keywords: Synthetic Cathinone; chiral separation; Tetralones; new psychoactive substances; 2-amino-α-tetralone synthesis; stereoizomerie; synthetic cathinones; Chromatography, High Pressure Liquid; tetralony; cirkulární dichroismus; on-line circular dichroism spectra; Circular Dichroism; syntetický kathinon; circular dichroism; vysokoúčinná kapalinová chromatografie; determination of absolute configuration; Stereoisomerism